DEVELOPMENTAL TENDENCIES AND THEORETICAL APPROACHES OF HOMEPAGES - Kukule, Ilze; Losane, Natalija (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2016)
The aim of the article is to explore Home pages development trends evaluating the Latvian Higher Education website design specifics.The methods of research: theoretical – investigation and analysis of relevant literature, internet sources and regulatory documents. Empirical – methods of data collecting group discussion; methods of data processing: comparative analysis, content analysis.